Thermodynamics of Cr3+-Cr6+ equilibrium in borate melts - Singh S.P.; Prasad G.; Nath P. (My University, 2025)
The Cr3+-Cr6+ equilibrium was studied in lithium and sodium aluminoborate melts in an air atmosphere at different temperatures. A mechanism of the Cr3+-Cr6+ redox reaction in glass melts has been suggested. Enthalpy and entropy of the reaction in molten borates were calculated and the results thus obtained have been discussed thermodynamically. © 1981 Chapman and Hall Ltd.